Antiproliferation and apoptosis on RKO colon cancer by Millingtonia hortensis - Tansuwanwong S. (2014)
Millingtonia hortensis is a medicinal plant widely used in many Asian countries. An aqueous crude extract of this plant has been shown the apoptosis induction on RKO colon cancer cells. However, its mechanism remains unknown. To learn more about this plant extract, we partially purified the crude extract using Sephadex LH-20 and three aqueous fractions were collected. Each fraction was investigated for cytotoxicity using MTT assay. Fraction 1 showed antiproliferative effect on RKO cells with dose-dependent manner, while fraction 2 and 3 had no effect. Induction of apoptosis was determined using flow cytometry and DNA fragmentation method. Apoptotic cell numbers and the appearance of fragmented DNA increased with dose-dependent manner after treatment with fraction 1 for 48 h. We further investigated the expression of apoptotic protein by western blot analysis. Fraction 1 decreased the expression of anti-apoptotic protein, Bcl-xL and p-Bad, while pro-apoptotic protein Bad, was not changed. Fraction 1 also decreased the expression of p-Akt and slightly increased the level of total Akt. These results indicated that fraction 1 is able to inhibit cell proliferation and induce apoptosis on RKO cells by decreasing the expression of Bcl-xL, p-Bad and p-Akt which are involving in survival of cancer cells. © 2008 Springer Science+Business Media, LLC.